Thiamine Deficiency and Cardiac Dysfunction in Cambodian Infants - Porter, Samuel G.; Coats, Debra; Fischer, Philip R.; Ou, Kevanna; Frank, Elizabeth L.; Sreang, Phivan; Saing, Soksan; Topazian, Mark D.; Enders, Felicity T.; Cabalka, Allison K. (The Journal of pediatrics, 2014)
To compare blood thiamine concentrations, echocardiography findings, and plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels in infants with clinically diagnosed beriberi and healthy matched controls, and to evaluate changes after thiamine treatment. Sixty-two Cambodian infants (20 cases and 42 controls), aged 2-47 weeks, were enrolled in this prospective study. Echocardiography and phlebotomy were performed at baseline and after thiamine treatment. Both cases and controls were thiamine-deficient, with median blood thiamine diphosphate (TDP) concentrations of 47.6 and 55.1 nmol/L, respectively (P = .23). All subjects had normal left ventricular ejection fraction. The median NT-proBNP concentration in cases (340 pg/mL [40.1 pmol/L]) was higher than previously reported normal ranges, but not statistically significantly different from that in controls (175 pg/mL [20.7 pmol/L]) (P = .10), and was not correlated with TDP concentration (P = .13). Two cases with the lowest baseline TDP concentrations (24 and 21 nmol/L) had right ventricular enlargement and elevated NT-proBNP levels that improved dramatically by 48 hours after thiamine administration. Only a minority of thiamine-deficient Cambodian infants demonstrate abnormal echocardiography findings. Thiamine deficiency produces echocardiographic evidence of right ventricular dysfunction, but this evidence is not apparent until deficiency is severe. NT-proBNP concentrations are mildly elevated in sick infants with normal echocardiography findings, indicating possible physiological changes not yet associated with echocardiographic abnormalities.